THE FIRST SHIA GROUPS OF IRAN (ZAYDIS, ISMAILIS, QARMATIANS, AND THE ROLE OF TWELVER SHIAS IN THE HISTORICAL DEVELOPMENT OF MALAKAT) - Makhsudova Madinakhon Latibjon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article provides an in-depth analysis of the emergence and evolution of the first Shia groups in Iran, namely the Zaydis, Ismailis, and Qarmatians, while also exploring the significant role of Twelver Shias in the historical development of Malakat, a key region in the Islamic world known for its cultural and intellectual contributions. The study delves into the theological foundations, political strategies, and socio-cultural impacts of these early Shia movements, emphasizing their influence on the religious identity of Iran and their broader contributions to Islamic civilization. Through a multidisciplinary approach that integrates historical research, religious studies, and cultural analysis, the article highlights the diversity within Shia Islam and its lasting legacy in shaping the political, intellectual, and cultural history of Malakat. The findings reveal that these early Shia groups not only played a crucial role in the formation of Iran’s religious landscape but also contributed to the intellectual and political dynamism of the Islamic world, particularly through their resistance against oppression, establishment of scholarly traditions, and promotion of social justice.